Baseline 4D Flow-Derived in vivo Hemodynamic Parameters Stratify Descending Aortic Dissection Patients With Enlarging Aortas - Chu, Stanley; Kilinc, Ozden; Pradella, Maurice; Weiss, Elizabeth; Baraboo, Justin; Maroun, Anthony; Jarvis, Kelly; Mehta, Christopher K.; Malaisrie, S. Chris; Hoel, Andrew W.; Carr, James C.; Markl, Michael; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose The purpose of our study was to assess the value of true lumen and false lumen hemodynamics compared to aortic morphological measurements for predicting adverse-aorta related outcomes (AARO) and aortic growth in patients with type B aortic dissection (TBAD). Materials and Methods Using an IRB approved protocol, we retrospectively identified patients with descending aorta (DAo) dissection at a large tertiary center. Inclusion criteria includes known TBAD with ≥ 6 months of clinical follow-up after initial presentation for TBAD or after ascending aorta intervention for patients with repaired type A dissection with residual type B aortic dissection (rTAAD). Patients with prior descending aorta intervention were excluded. The FL and TL of each patient were manually segmented from 4D flow MRI data, and 3D parametric maps of aortic hemodynamics were generated. Groups were divided based on (1) presence vs. absence of AARO and (2) growth rate ≥ vs. < 3 mm/year. True and false lumen kinetic energy (KE), stasis, peak velocity (PV), reverse/forward flow (RF/FF), FL to TL KE ratio, as well as index aortic diameter were compared between groups using the Mann–Whitney U or independent t-test. Results A total of n = 51 patients (age: 58.4 ± 15.0 years, M/F: 31/20) were included for analysis of AARO. This group contained n = 26 patients with TBAD and n = 25 patients with rTAAD. In the overall cohort, AARO patients had larger baseline diameters, lower FL-RF, FL stasis, TL-KE, TL-FF and TL-PV. Among patients with de novo TBAD, those with AAROs had larger baseline diameter, lower FL stasis and TL-PV. In both the overall cohort and in the subgroup of de novo TBAD, subjects with aortic growth ≥ 3mm/year, patients had a higher KE ratio. Conclusion Our study suggests that 4D flow MRI is a promising tool for TBAD evaluation that can provide information beyond traditional MRA or CTA. 4D flow has the potential to become an integral aspect of TBAD work-up, as hemodynamic assessment may allow earlier identification of at-risk patients who could benefit from earlier intervention.